(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
In the digital age, teaching reading has evolved significantly with the integration of digital tools and eBooks. This article explores effective strategies for teaching reading using these modern resources to enhance engagement, comprehension, and learning outcomes for students. Digital tools such as interactive eBooks, online reading platforms, and multimedia content provide unique opportunities to support diverse learning styles and increase student interaction with texts. Through the use of embedded multimedia elements like audio, video, and hyperlinks, eBooks offer a dynamic approach that fosters deeper understanding and engagement.